Facts about Bottled Water - Leila M. Kalley; Karla P. Shelnutt (EDIS)
FCS8887, a 3-page illustrated fact sheet by Leila M. Kalley and Karla P. Shelnutt, addresses concerns about bottled water safety. Includes a list of recommended Web sites. Published by the UF Department of Family Youth and Community Sciences, February 2010.